2019
DOI: 10.18502/ijaai.v18i1.631
|View full text |Cite
|
Sign up to set email alerts
|

Expression Levels of Predominant Adipokines and Activations of STAT3, STAT6 in an Experimental Mice Model of Obese Asthma

Abstract: Obese asthma is a new asthma phenotype. The underlying mechanisms are not clearly understood. Leptin and adiponectin are two predominant adipokines produced by adipose tissue. Studies have demonstrated a role of leptin on regulating the Janus kinase/signal transducer and ativator of transcription protein (JAK/STAT) signaling pathway and STAT3, STAT6 were known to have essential role on inflammatory cytokines production. However, whether STAT3 and STAT6 are activated and related to leptin merit further investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…Bruno et al (38) revealed that in the airway epithelial cells, the expression levels of leptin and its receptor LEPR were higher in normal subjects than in smokers or in patients with mild-to-severe COPD. In a previous study, it was also revealed that the expression level of leptin in the BALF was significantly increased in obese mice with asthma (39). Thus, it is conceivable that obesity-associated increases in airway leptin may have an effect on the airway inflammation of asthma.…”
Section: Discussionmentioning
confidence: 91%
“…Bruno et al (38) revealed that in the airway epithelial cells, the expression levels of leptin and its receptor LEPR were higher in normal subjects than in smokers or in patients with mild-to-severe COPD. In a previous study, it was also revealed that the expression level of leptin in the BALF was significantly increased in obese mice with asthma (39). Thus, it is conceivable that obesity-associated increases in airway leptin may have an effect on the airway inflammation of asthma.…”
Section: Discussionmentioning
confidence: 91%
“…Less is known about leptin-mediated molecular mechanisms in human airway inflammation and asthma. However, in recent years, different studies conducted on human bronchial cells [95,96] or mice models of obese asthma [97] have shed some light on this mechanism. Hao et al [95] and Watanabe et al [96] analyzed the effect of leptin on human bronchial epithelial cells' cultures (HBE16) and human lung fibroblasts, respectively (NHLFs).…”
Section: Pro-inflammatory Adipokines: Leptin and Resistinmentioning
confidence: 99%
“…These cytokines would recruit inflammatory cells, induce cells' degranulation and myofibroblasts differentiation, contributing to asthma exacerbation and epithelial remodeling. With regard to animal models, Chong et al [97] designed a mice model of obese asthma and after sensitization with intra-parenteral ovalbumin, the animals were sacrificed and bronchoalveolar lavage fluid was collected in order to analyze leptin levels and expression of cellular transcriptional and translational factors. According to their results, leptin levels were higher in Bronchoalveolar lavage (BALF) from obese and asthma-induced animals when compared with non-obese asthmatic and non-asthmatic mice.…”
Section: Pro-inflammatory Adipokines: Leptin and Resistinmentioning
confidence: 99%
“…However, metformin did not affect ozone-induced inflammation in female db/db mice (Shore et al, 2008). Changes in leptin in males were similar to the shift in females (Chong et al, 2019). Many studies have demonstrated that leptin promotes pulmonary inflammation by activating the STAT3 signaling pathway (Zhu et al, 2019).…”
Section: Male Obesity-related Asthma Mouse Modelsmentioning
confidence: 72%
“…Similar to the female model, male obese asthmatic mice exhibited increased neutrophils and Th17 cells (Zhu et al, 2019). The inhibition of Notch signaling can suppress the Th17 response and alleviate AHR in obese asthmatic mice (Zeng et al, 2019).…”
Section: Male Obesity-related Asthma Mouse Modelsmentioning
confidence: 82%